Development of Multi-Filtration Method in Waste Treatment of PT "X" Glasses Industry in Surabaya - Hendra Yuda; Agus Budianto (Jurnal Teknologi dan Manajemen, 2023)
The wastewater treatment plant (WWTP) is an important instrument for the industrial world to treat its liquid waste so as not to endanger the environment. The eyeglass lens industry has wastewater that has a very high level of turbidity due to residual sediment from the lens cutting and scrubbing process. The treatment of liquid waste with a filtration system aims to reduce the value of TSS, COD, pH, Oil and Grease and observe BOD, so that it is hoped that the treated water can be clearer to be used as raw water for the next process (Re-Use). Experimental results from research with physical tests using filtration or membrane methods show the levels of TSS previously 46.033 mg/L to 2.5 mg/L, pH previously 6.9 to 7.1, COD previously 373.3 mg/L to 265 mg/L, Oil Grease previously 2.88 mg/L to 2.03 mg/L, and BOD5 previously 100.2 mg/L to 105.4.Â